2007
DOI: 10.1017/s1751731107000705
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of offspring following supplementation of sow diets with oil during early to mid gestation

Abstract: The role of dietary fat during early pregnancy in sows has not yet been fully established. The aim of the study was to determine the consequences of altering the fatty acid profile of sow diets during the first half of gestation; oils of different fatty acid composition were chosen as energy supplements to provide diets with different fatty acid profiles. A group of 48 multiparous sows were used to evaluate the effects of supplemental feeding during the first 60 days of gestation (term ≈ 115 days). Sows were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Due to the similarities in the fatty acid metabolism in human and pigs [21] and in order to test our hypothesis, this study aimed to determine the consequences of modifying the fatty acid composition of sows' diets, using dietary supplements with olive oil (OO) or fish oil (FO), during the first or the second half of gestation on the fatty acid profiles of maternal plasma and milk during lactation and in plasma of suckling neonates. The present study is a continuation of previous ones using the same treatment protocol in pregnant sows where it was found that with the exception of a slightly improved growth performance in offspring of FO fed sows, no difference was found in reproductive performance between the two groups [22][23][24][25].…”
Section: Introductionsupporting
confidence: 67%
“…Due to the similarities in the fatty acid metabolism in human and pigs [21] and in order to test our hypothesis, this study aimed to determine the consequences of modifying the fatty acid composition of sows' diets, using dietary supplements with olive oil (OO) or fish oil (FO), during the first or the second half of gestation on the fatty acid profiles of maternal plasma and milk during lactation and in plasma of suckling neonates. The present study is a continuation of previous ones using the same treatment protocol in pregnant sows where it was found that with the exception of a slightly improved growth performance in offspring of FO fed sows, no difference was found in reproductive performance between the two groups [22][23][24][25].…”
Section: Introductionsupporting
confidence: 67%
“…The present experiment confirmed that the fatty acid profile in sows' colostrum and mature milk, blood plasma, and plasma of their progeny was influenced by the dietary fatty acid profile of oil sources. Previous studies revealed the impact of maternal diet provided during late gestation and lactation differing in fatty acid composition on sows' colostrum and mature milk composition [2,6,12,14,15]. However, the present experiment is the first one using the oil obtained from hemp seeds for sow nutrition.…”
Section: Discussionmentioning
confidence: 85%
“…Manipulation of the content and composition of dietary fat in sow diets during late gestation and lactation seems one of the promising methods to influence fat content and composition of colostrum and mature milk, thereby improving the development of the immune system in early life and robustness of their progeny [2,11]. While a great number of studies described the impact of supplementing different fat sources for sow diets during the late gestation and lactating period with regard to performance of sows and their progeny, there is less evidence in the literature describing the comparison of rapeseed oil, coconut oil, palm oil, sunflower oil, fish oil [2,12], lard and fish oil [13] or inclusion of various levels of tuna oil [6], olive oil [8,14,15] and soybean oil [16] with regard to biological responses of the piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation of placental development by maternal nutrition, during early–mid-gestation, is therefore likely to have direct consequences for fetal nutrition and development. Our previous work ( 21 ) suggests that energy supplementation and the fatty acid profile of the maternal diet during the first half of gestation influence the growth and development of piglets both in utero and during postnatal life. Since LBW has previously been linked to placental insufficiency ( 22 ) and placental development occurs during the first half of gestation ( 23 , 24 ) , it seems probable that the maternal diet during early gestation will also have some influence upon the incidence of LBW.…”
mentioning
confidence: 99%